MODERN REQUIREMENTS FOR REACTIVE POWER COMPENSATION IN MAIN ELECTRICAL NETWORKS - KUCHANSKY, VLADYSLAV; KOSHMAN, VSEVOLOD; SHEVCHUK, VITALIY; SABARNO, LYUDMILA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The main requirements for reactive power compensation in extra-high voltage AC power transmission systems are outlined. A flowchart for planning reactive power compensation using controlled shunt reactors and static synchronous compensators is presented. Standardization of extra-high voltage AC power transmission systems on the basis of the International Electrotechnical Commission is currently in full swing. In 2013, IEC established a technical committee, TC 122, which prepares relevant standards for systems with operating voltages above 800 kV. IEC/TC 122 specialists prepare and disseminate system-level specifications used for the design, construction and operation of EHV platforms. At the same time, they publish standards for specific equipment. Cooperation with CIGRE In the field of standardization of engineering solutions under consideration, IEC closely cooperates with the International Council for Large High Voltage Electrical Systems (Conseil international des grands réseaux électriques; CIGRE). This global membership organization develops and publishes relevant technical documents in the field of power systems, sharing knowledge and experience with stakeholders. IEC and CIGRE began their collaboration on the standardization of extra-high voltage transmission systems after a joint international symposium on EHV platforms held in Beijing, China, in 2007. IEC/TC 122 work programme According to IEC/TC 122 representatives, the integration of technical expertise from all stakeholders is key to the development of balanced international standards. Since 2014, IEC/TC 122 has published three technical specifications and one technical report. Technical report IEC TS 63042-100:2016 "Extra-high voltage AC transmission systems - Part 100: General information" provides an overview of the guidelines and standards for extra-high voltage AC transmission systems prepared to ensure the reliability and availability of such solutions, taking into account environmental aspects. their construction and operation. Published technical specifications contain information on the requirements for extra-high voltage AC transmission systems relating to voltage regulation and insulation design, substation design and acceptance tests. These are the following documents: • IEC TS 63042-101:2019 "Extra-high voltage AC transmission systems - Part 101: Design of insulation and voltage regulation systems"; • IEC TS 63042-201:2018 "Extra-high voltage AC transmission systems - Part 201: Design of substations for extra-high voltage AC transmission"; • IEC TS 63042-301:2018 "Extra-high voltage AC transmission systems - Part 301: On-site acceptance tests"; Currently, the work of the experts of the IEC/TC 122 technical committee covers the following areas: general issues of system design, transmission line design, commissioning and guidelines for measuring frequency parameters of EHV AC transmission lines.
Keywords: reactive power compensation; controlled shunt reactor; international electrotechnical commission; extra-high voltage AC systems